2019
DOI: 10.1002/hep4.1441
|View full text |Cite
|
Sign up to set email alerts
|

Nontranscriptional Activity of Interferon Regulatory Factor 3 Protects Mice From High‐Fat Diet‐Induced Liver Injury

Abstract: Interferon regulatory factor 3 (IRF3) has both transcriptional and nontranscriptional functions. Transcriptional activity is dependent on serine phosphorylation of IRF3, while transcription‐independent IRF3‐mediated apoptosis requires ubiquitination. IRF3 also binds to inhibitor of nuclear factor kappa B kinase (IKKβ) in the cytosol, restricting nuclear translocation of p65. IRF3‐deficient mice are highly sensitive to high‐fat diet (HFD)‐induced liver injury; however, it is not known if transcriptional and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
(86 reference statements)
0
27
0
Order By: Relevance
“…IRF3 is best known for its function as a transcription factor, mediating the upregulation of not only type I IFN but also a small subset of “IFN-independent” ISGs ( 28 30 ). In order to determine whether apoptosis requires IRF3 transcriptional activity, IRF3 −/− PK-15 cells stably expressing a FLAG-tagged transcriptionally inactive IRF3 mutant (S394A S396A) termed “S1” ( 31 , 40 ) were generated using lentivirus ( Fig. 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…IRF3 is best known for its function as a transcription factor, mediating the upregulation of not only type I IFN but also a small subset of “IFN-independent” ISGs ( 28 30 ). In order to determine whether apoptosis requires IRF3 transcriptional activity, IRF3 −/− PK-15 cells stably expressing a FLAG-tagged transcriptionally inactive IRF3 mutant (S394A S396A) termed “S1” ( 31 , 40 ) were generated using lentivirus ( Fig. 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…All three of these inducers contribute to liver injury, implicating IRF3 in the development of liver disease pathology. Studies through our work revealed that RIPA in restorative hepatic monocytes contributes to ethanol-induced liver injury in an acute-on-chronic hepatitis model [ 59 ]. In contrast, we further showed that the non-transcriptional RIPA activity of IRF3 plays a protective role in high-fat diet-induced liver injury [ 59 ].…”
Section: Role Of Irf3 As a Mediator Of Innate Immune Responses To Viral Infectionmentioning
confidence: 99%
“…Studies through our work revealed that RIPA in restorative hepatic monocytes contributes to ethanol-induced liver injury in an acute-on-chronic hepatitis model [ 59 ]. In contrast, we further showed that the non-transcriptional RIPA activity of IRF3 plays a protective role in high-fat diet-induced liver injury [ 59 ]. Therefore, while we have shown the activation of IRF3-driven apoptosis in virus infections benefits the host, the role of IRF3 in liver disease still remains somewhat unclear.…”
Section: Role Of Irf3 As a Mediator Of Innate Immune Responses To Viral Infectionmentioning
confidence: 99%
“…DMSO was used as vehicle control for auranofin. For palmitic acid treatment, palmitic acid was prepared in BSA-containing DMEM, as described before (15), at the final indicated concentrations and added directly to the culture media for the indicated length of treatment.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In a recent study using nontranscriptional IRF3 expressing mice, we demonstrated that the nontranscriptional activity of IRF3 is sufficient to induce numerous markers of hepatocellular damage in response to ethanol, including increased ALT/AST, triglycerides, and inflammatory cytokine expression ( 14 ). In contrast, nontranscriptional IRF3 activity plays a protective role in mice from HFD-induced liver injury partially through the suppression of NF-κB signaling ( 15 ).…”
mentioning
confidence: 99%